2017
DOI: 10.1021/acs.cgd.7b01325
|View full text |Cite
|
Sign up to set email alerts
|

A Large Family of Halogen-Bonded Cocrystals Involving Metal–Organic Building Blocks with Open Coordination Sites

Abstract: We demonstrate a design for halogen-bonded metal−organic cocrystals involving coordinatively unsaturated square-planar Cu(II) and Ni(II) centers, by utilizing a Schiff base ligand whose pendant acetyl group enables halogen bonding. The robustness of this design is evident by the assembly of a large family of eight cocrystals based on zero-, one-, and twodimensional halogen bonded architectures involving mono-or ditopic halogen bond donors based on iodine or bromine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…[9][10][11][12][13] In contrast, the use of halogen bonding in coordination complexes, which are among the most diverse structures found in chemistry, remains comparatively unexplored. 14 In the studies that have been reported, three general strategies have emerged: firstly the design of ligands with an acceptor and donor in the same ligand (type i), [15][16][17] secondly cocrystals with either a neutral or cationic complex and halogen bonding donors (type ii) [18][19][20][21][22][23][24] and lastly complexes with two different ligands with one acting as the acceptor and the other the donor (type iii). The latter class typically uses halopyridine ligands and chelates such as -diketonates to balance the charge of the metal and satisfy the need for octahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In contrast, the use of halogen bonding in coordination complexes, which are among the most diverse structures found in chemistry, remains comparatively unexplored. 14 In the studies that have been reported, three general strategies have emerged: firstly the design of ligands with an acceptor and donor in the same ligand (type i), [15][16][17] secondly cocrystals with either a neutral or cationic complex and halogen bonding donors (type ii) [18][19][20][21][22][23][24] and lastly complexes with two different ligands with one acting as the acceptor and the other the donor (type iii). The latter class typically uses halopyridine ligands and chelates such as -diketonates to balance the charge of the metal and satisfy the need for octahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been substantial studies into halogen bonding in single component metal-organic solids [30][31][32][33][34][35][36][37][38][39][40][41], synthesis of multi-component materials based on halogen-bonded metal-organic components has been receiving much less attention. Particularly scarce are studies involving cocrystals of neutral metal-organic components acting as halogen bond acceptors [42][43][44][45][46][47]. The most promising building blocks to date have been metal coordination complexes comprised of pendant acceptor groups such as halogenide ligands [46,47], chelating ligands such as imines [43], β-dicarbonyl compounds [14] and ligands with additional (non-coordinating) electron rich atoms or groups such as morpholine or thiomorpholine [48,49], which can form cocrystals with halogen bond donors, such as perfluorinated iodobenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly scarce are studies involving cocrystals of neutral metal-organic components acting as halogen bond acceptors [42][43][44][45][46][47]. The most promising building blocks to date have been metal coordination complexes comprised of pendant acceptor groups such as halogenide ligands [46,47], chelating ligands such as imines [43], β-dicarbonyl compounds [14] and ligands with additional (non-coordinating) electron rich atoms or groups such as morpholine or thiomorpholine [48,49], which can form cocrystals with halogen bond donors, such as perfluorinated iodobenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…Halogen bond (XB) has found to be a useful tool in crystal engineering in recent years due to its strength and directional preferences [1][2][3][4][5][6]. A molecular entity with electrophilic region on a halogen atom is defined as XB donor, while an entity with nucleophilic region, i.e., Lewis base, is defined as an XB acceptor [7].…”
Section: Introductionmentioning
confidence: 99%